Plataforma Zooppa e a resistência criativa: nasce uma nova fase na publicidade; surge uma nova instância de produção - Brito , Fellipe Gustavo Rocha Mousinho de (2013)
Through democratization of production tools and inserted onto a participatory culture, users start to produce and share their own content, reconfiguring traditional practices and constituting new productive instances. By this change in production’s flow, where the consumer assumes both the role of spectator and the producer of information, various media segments start to have their activities modified, and also reaching actual advertising. From this interaction made possible by the medium, advertising announcements cease to be designed exclusively by specialized agencies and individuals and start being developed by the own consumers, which we have classified in this study as actions of the Participatory Advertising. Featuring an innovative way of producing advertising, such as the 'advertising developed by the consumer’, we start from the examination of an original element of this practice: the social network Zooppa, understood as a collaborative platform inserted into this production model. Thus, the current research aimed at analyzing this new production system, verifying the manners that this website and this productive heterogeneous type of capital enable the reconfiguration of the advertising practice, constituting a new phase. Through the results obtained in the study, we could confirm the beginning of a phase of our advertising as defined in this study as Phase Resistance.